The Influence of Organizational Justice on the Organizational Commitment of Personnel in South-West Nigerian Public University Libraries - Adewoyin, Omobola Olufunke (University of Dar es Salaam Library Journal, 2022)
For university libraries to achieve their set goals and objectives, a committed workforce is indispensable. Several factors could enhance the commitment of library personnel. However, studies have not given adequate attention to the influence of organizational justice on the organizational commitment of library personnel in Nigeria. This study, therefore, investigated the influence of organizational justice on the organizational commitment of library personnel in public universities in South-West Nigeria. A survey research design was adopted. A total remuneration was used. Findings showed that organizational justice had a significant influence on organizational commitment of library personnel. The findings also revealed that distributive justice and interactional justice significantly influenced the affective commitment of library personnel while procedural justice was not significant. Furthermore, distributive justice and interactional justice had a significant influence on the continuance commitment of library personnel while procedural justice had no significant effect on the continuance commitment of library personnel. The study concluded that organizational justice increased organizational commitment of library personnel in public universities. The study would serve as a contribution towards solving the challenges of lack of organizational commitment in academic libraries. It was recommended that library management should involve the personnel in their decision-making processes.